Estimation of Probable Maximum Precipitation (PMP) in the Garrudbar Dam Watershed - Mojtaba Farhadzadeh; Mojtaba Farhadzadeh; پریسا ملکی (مهندسی و مدیریت ساخت)
Precipitation is one of the most important yet highly variable atmospheric parameters. Its magnitude differs across regions depending on geographical location and prevailing atmospheric conditions. The Garrudbar Dam is located on the Shesh Rudbar River, one of the headwaters of the Talar River, in the central part of Savadkouh County, Mazandaran Province. The objective of this study is to estimate the Probable Maximum Precipitation (PMP) in the Garrudbar Dam watershed and analyze extreme rainfall events for specific durations in this region. To assess the annual precipitation in the watershed, data from the meteorological station located within the study area (Paland) and neighboring stations were utilized over a 56-year statistical period (1966–2022). The PMP values for the stations were calculated using the Hershfield method. Subsequently, the area reduction method was employed to estimate the basin-wide PMP for the watershed. The final results indicate that the PMP for the Garrudbar Dam watershed, covering an area of 186 km², is estimated to be 237 mm. Additionally, the analysis of extreme rainfall events for specific durations demonstrated that the Gumbel probability distribution function outperforms the two-parameter log-normal distribution. Consequently, the periodic rainfall values for different return periods were determined using the Gumbel distribution.